2021
DOI: 10.1177/00031348211038580
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Clinical and Patient-Reported Outcomes After Transversus Abdominis Release for Complex Hernia Repair With a Review of the Literature

Abstract: Purpose Posterior component separation with transversus abdominis release (TAR) enables medial myofascial flap advancement in complex abdominal wall reconstruction. Here, we add to a growing body of literature on TAR by assessing longitudinal clinical and patient-reported outcomes (PROs) after complex ventral hernia repair (VHR) with TAR. Methods Adult patients undergoing VHR with TAR between 10/15/2015 and 1/15/2020 were retrospectively identified. Patients with parastomal hernias and <12 months of follow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 33 publications
3
14
0
Order By: Relevance
“…Wound complications reported in comparable studies (SSO 3-39%, SSE 3-14%, SSOPI 3-12%) resemble the results reported here, except for SSE (23%), which was high in the first episode (8,11,13,15,18,20,(45)(46)(47)(48)(49). While SSE is underreported in most studies, and no specific cause can be designated, this may be related to the TAR learning curve (8,13,15,48,49). The rate of patients without any systemic complication cannot be deduced in any other study, nor can it be adequately compared with our results.…”
Section: Evaluation Of Outcomessupporting
confidence: 86%
See 3 more Smart Citations
“…Wound complications reported in comparable studies (SSO 3-39%, SSE 3-14%, SSOPI 3-12%) resemble the results reported here, except for SSE (23%), which was high in the first episode (8,11,13,15,18,20,(45)(46)(47)(48)(49). While SSE is underreported in most studies, and no specific cause can be designated, this may be related to the TAR learning curve (8,13,15,48,49). The rate of patients without any systemic complication cannot be deduced in any other study, nor can it be adequately compared with our results.…”
Section: Evaluation Of Outcomessupporting
confidence: 86%
“…Textbook Outcome increased to 55% and rate and severity of both wound and systemic and complications was further reduced: SSO to 20% (p = 0.03), SSE 10% (p = 0.02), SSOPI 5% (p = 0.07), Unintended contamination of the surgical field (complete bowel lesions), n (%) 3 (15) 3 ( 43) 1 ( 10) 1 ( 25) 8 ( 28) 0.728…”
Section: Outcome Evaluation After the Third Episode Of 20 Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous studies have affirmed the positive short-term outcomes of TAR in terms of QoL, recurrence rates, and functionality, solidifying its status as an effective surgical solution for large and complex abdominal defects. [21][22][23][24][25][26][27] Surgical site occurrences tended to occur at similar rates to other VHR techniques. Seroma and delayed healing were the most frequently reported complications, whereas more severe complications such as mesh explanation and reoperations occur less frequently.…”
mentioning
confidence: 76%